A Novel Intrinsic Force Sensing Method for Robot Manipulators during Human-Robot Interaction - Kim, Uikyum; Jo, Gwanghyun; Jeong, Heeyeon; Park, Cheol Hoon; Koh, Je Sung; Park, Dong Il; Do, Hyunmin; Choi, Taeyong; Kim, Hwi Su; Park, Chanhun (IEEE Transactions on Robotics, 2021)
Robotic manipulators require contact force sensing capabilities to sense the contact force between the manipulator and an object. Specifically, for humans and robots to coexist in the work environment, the robot must be able to detect an external force applied by a human. This study presents a new intrinsic force sensing method for robot manipulators that can obtain accurate information of the external force applied by a human during human-robot interaction. The method employs a robot cover, which is typically utilized in robot manipulators. Unlike conventional force sensing methods, a six-axis force/torque sensor is placed between the cover and the link of the robot manipulator. As a result, the proposed method provides information of the three-axis contact force applied to the cover surface and its contact location. Therefore, the cover itself becomes a sensorized cover based on the intrinsic force sensing method. To evaluate its sensing performance, the sensorized cover is experimentally validated using reference sensors. Finally, an experiment is performed in which the robot successfully recognizes letters written on the cover, indicating a high level of contact force sensing performance.
Keywords: Contact location; Reference sensors; Robot interactions; Robot manipulator; Robotic manipulators; Sensing performance; Six-axis force/torque sensor; Work environments; Contact location; human-robot interaction (HRI); intrinsic force sensing; six-axis force/torque (F/T) sensor; three-axis force